OBJECTIVES ATTAINABLE THROUGH ACCOUNTING RESEARCH. - Nerlove, S. H. (The Accounting Review, 1935)
Abstract Adopting Professor Henry Rand Hatfield's broad statement of the function of accounting, the possible objectives of accounting research are almost unlimited. Professor Hatfield once stated that the function of accounting is "to place responsibility, to prevent fraud, to guide industry, to determine equities, to solve the all essential conundrum of business. In order to perform this function adequately it is essential for accountants to take full cognizance of the outstanding characteristics of modern business life, to develop and to use effectively available tools of analysis and to recognize in all respects their social responsibilities. The author in this papers confines himself to a series of observations regarding the weakness of present-day accountancy, which will readily bring to mind certain desirable objectives to be attained through accounting research. According to the author, with accountants becoming business advisers, exponents of good financial practice, and fiscal agents of stockholders, the objectives which he had suggested to be attained through accounting research, in view of certain shortcomings of present-day accountancy, may even be too narrow rather than too broad.